Assortative matching on income - Pierre-André Chiappori; Carlo V. Fiorio; Alfred Galichon; Stefano Verzillo (European Commission, 2022)
We analyze marital matching on income using an extremely rich Dutch data set containing all income tax files over four years. We develop a novel methodology that directly extends previous contributions to allow for highly flexible matching patterns. Investigating all marriages that took place between 2011 and 2014, we find that marital patterns remain remarkably stable over the period. While a majority of couples match assortatively, a small but significant minority display negative assortative matching. We also show that standard approaches, which consider all married couples using current incomes, may generate misleading conclusions. Finally, we find that, in contrast with recent results, whether his income exceeds her does not seem to play any significant role.
Keywords: 330